2018
DOI: 10.17219/pim/96288
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effect of X-ray irradiation on the structure of Narafilcon A biopolymer soft contact lenses

Abstract: Background. The effects of external factors such as X-ray irradiation on the structure and physical properties of contact lenses are very important for both the patients using contact lenses and medical personnel. Objectives. The aim of the study was to investigate the effect of X-rays on the structure of Narafilcon A silicone-hydrogel contact lenses. Material and methods. In order to study the structural changes caused by X-rays in Narafilcon A polymer contact lenses, the following spectroscopy methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…An increased total irradiation dose decreased the free volume size and slightly increased the number of free volumes. The X-rays did not affect the microstructure in a negative way and did not cleave monomer bonds [ 115 ]. Calcium deposits were investigated in PHEMA soft contact lenses (Soflens and Super Soft).…”
Section: Resultsmentioning
confidence: 99%
“…An increased total irradiation dose decreased the free volume size and slightly increased the number of free volumes. The X-rays did not affect the microstructure in a negative way and did not cleave monomer bonds [ 115 ]. Calcium deposits were investigated in PHEMA soft contact lenses (Soflens and Super Soft).…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies on polymer materials used in medicine have developed rapidly in recent years, e.g., for the production of contact lenses. In another study Filipecka et al [20], of was to examine changes in the polymer structure of Narafilcon A soft siliconehydrogel contact lenses (a very popular type of contact lens) due to exposure to X-ray irradiation. The finding showed that X-ray radiation did not affect or damage polymer bonds and can in the future contribute to the use of X-ray and γ-radiation to sterilize contact lenses.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%